2018
DOI: 10.1080/15555240.2018.1521725
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the usability of two salutogenic instruments on health and work experience, using cognitive interviewing

Abstract: Workplace surveys are used in workplace health promotion as a basis for improvements at the workplace. But there is lack of psychometrically and qualitatively validated work-health related instruments with a salutogenic approach. The purpose of this study was, therefore, to evaluate the two instruments, the Salutogenic Health Indicator Scale and the Work Experience Measurement Scale, among staff of different professions in a healthcare setting. These instruments were evaluated with cognitive interviews conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The overall internal consistency was excellent (α = 0.92) (Bringsén et al, 2009). Further validation using cognitive interviews (n = 14) confirmed its high qualitative validity (Nilsson Lindström et al, 2018). The SHIS-FI has recently been validated in Finnish care workers (n = 2117), showing excellent internal consistency (α = 0.94) (Hult & Välimäki, 2023).…”
Section: Salutogenic Health Indicator Scalementioning
confidence: 75%
“…The overall internal consistency was excellent (α = 0.92) (Bringsén et al, 2009). Further validation using cognitive interviews (n = 14) confirmed its high qualitative validity (Nilsson Lindström et al, 2018). The SHIS-FI has recently been validated in Finnish care workers (n = 2117), showing excellent internal consistency (α = 0.94) (Hult & Välimäki, 2023).…”
Section: Salutogenic Health Indicator Scalementioning
confidence: 75%
“…Alignment with integrated approach domains: determining whether an instrument can assess 'prevent harm', 'promote the positive', 'respond to problems' or all three domains: The FlourishDX and Guarding Minds at Work resources were the only instruments located that were relevant to all three domains of an integrated approach to workplace mental health [25,26]. A total of 8% of instruments were relevant to multiple domains, being 'prevent harm' and 'promote the positive' (n = 6) [27][28][29][30][31][32] and 'prevent harm' and 'respond to problems' (n = 2) [33,34]. No instruments, aside from FlourishDX and Guarding Minds at Work, were relevant to the 'promote the positive' and 'respond to problems' domains together.…”
Section: Results and Synthesis Of Individual Sources Of Evidencementioning
confidence: 99%
“…The Canadian National Standard exemplifies one integrated approach that has already been employed in policy and practice in Organization for Economic Co-operation and Development (OECD) countries [6,7,133]. Six other instruments were relevant to the 'prevent harm' and 'promote the positive' domains, with some crossover observed during the mapping exercise [27][28][29][30][31][32]. It was noticeable, when reviewing these instruments, that a scale for assessing a psychosocial hazard, such as poor social support, may also be suitable for assessing the presence of a positive factor, such as social capital.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the motivation for translating the SHIS in this study can be justified based on its robust psychometric properties, comprehensive assessment of salutogenic factors and practical considerations supported by relevant literature (Bringsén et al, 2009;Hult & Valimaki, 2023;Nilsson Lindström et al, 2018;Persson et al, 2018). In this context, the aim of this study was to assess the validity and reliability of the SHIS, which was developed by Bringsén et al (2009), among a sample of Turkish university students in terms of its ability to account for psychosocial dimensions, capacities and health resources.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, several tools have been identified for measuring salutogenic health (Becker et al, 2008, 2009; Van Vliet et al, 2021). Various studies have demonstrated the robust psychometric properties and validity of the Salutogenic Health Indicator Scale (SHIS) (Hult & Valimaki, 2023; Nilsson Lindström et al, 2018). Nilsson Lindström et al (2018) conducted cognitive interviews to assess the validity of the SHIS, and the results indicated its high validity from a qualitative perspective.…”
Section: Introductionmentioning
confidence: 99%